Effects of Using Experiential Learning to Improve Knowledge, Awareness and Behavior of Healthy and Media Literacy Food Consumption in Prathom Suksa Students in Trang Province - Rakthai, Duangkhae; Cheeprasop, Nittaya; Singhasaem, Prapaipis; Suwanwela, Sopit; Leartwanawattana, Janpen (Princess of Naradhiwas University Journal, 2021)
This quasi-experimental study design aimed to study the effects of experience-based learning program on knowledge, awareness and behaviors of healthy consumption and media literacy food consumption of students in Prathom Suksa 4 to 6 in Muang District, Trang Province. The sample schools were randomly assigned into trial and control group which were consisted of 42 and 41 students from Prathom Suksa 4 to 6, respectively. The trial group received experience-based learning program. The control group received normal learning management. The research instrument was the program of experiential learning to create knowledge and awareness about healthy and media literacy food consumption for students in Prathom Suksa 4 to 6. Data was collected using the knowledge, awareness and behavioral questionnaires for healthy and media literacy food consumption. The reliability of the knowledge (KR-20), awareness and behavior questionnaires (Cronbach’s Alpha Coefficient) were .68, .78 and .72, respectively. Data were analyzed using descriptive statistic and t-test. The results showed that the post-trial scores of knowledge, awareness and behavior of the trial group were higher than before the trial and higher than the control group at statistically significance p <.05. (t = 14.99, 8.01 and 10.38, respectively). The experience-based learning program is effective and should be recommended to use as a guideline to increase knowledge, awareness and behavior in healthy consumption and media literacy food consumption for students in Prathom Suksa 4 to 6.